(untitled) (Journal of Hama University, 2024)
The goal of the current research is to identify the level of psychological flexibility on a sample of married female students at Tishreen University, and to identify the difference on the measure of psychological flexibility according to the variables of the presence of children, proximity to the husband’s family, and place of residence among the sample members. The psychological flexibility scale prepared by (Conner & David Resilience Scale, 2003) was used, translated by (Al-Hashimiyeh, 2017). The scale had good validity coefficients, as the value of the Cronbach’s alpha coefficient reached (0.75). The results showed that the level of psychological flexibility was weak, while there were no statistically significant differences on the scale according to the variables of the presence of children, proximity to the husband’s family, and place of residence among married female students at Tishreen University.